The cult of Confucianism - Abdraimova, B. B.; Assanova, A. B. (Journal of Oriental Studies, 2016)
The article defines how the life of Confucius, his experience and thoughts are extended to the students, his name became a symbol of the wisdom of the people, and the memory of his life, his unique personality to these days. Ethical teachings of Confucius for the basis of the Chinese mentality, becoming a major factor astonishing vitality of Chinese civilization